The Challenges of Democratic Governance in Nigeria’s Fourth Republic - Ogbonnaya, Ufiem Maurice; Omoju, Oluwasola Emmanuel; Udefuna, Nnadozie Patrick (Richtmann Publishing, 2012)
This paper examined the nature and dimension of such challenges as electoral malpractice, inter- and intra-ethniccleavages, religious crises and insecurity, weak democratic institutions and institutionalized corruption, which have confronteddemocratic governance in Nigeria since the Fourth Republic in 1999. It predominantly utilized secondary data. Findings showedthat these challenges threaten the consolidation of democratic formula capable of carrying the Nigerian state out of its endemiccycle of democratic and leadership crises. Despite these challenges, the paper observed that democracy in Nigeria has theprospects of creating enabling environment for good governance. Thus, the paper recommended that for these prospects to berealized, democratic principles in Nigeria must be consolidated and institutions strengthened.